THE (TRANS)FORMATION OF THE CONTEMPORARY FAMILY IN THE CHRONICLE JA NAO SE FAZEM PAIS COMO ANTIGAMENTE, OF LOURENCO DIAFERIA - Abreu Pinto, Aroldo Jose [UNESP]; Santos, Simeire da Silva (Univ Estado Mato Grosso, 2023)
This summary of reflections aimed to evidence some aspects of the chronic Ja nao se fazem pais como antigamente, by Lourenco Diaferia, both by the form as by the contente represented. We believe that, perceiving certain nuances proposed in the diaferian narrative, the reader, in addition to supplying at first moment his basic needs for fiction and fantasy, he comes into contact with a world view that view that subverts, right from the title, na established patriarchal view of the family and the behavior of children, with a critical view of the social and profile transformations that the 21st century families go through. As theorrtical and methodological support, we used the concepts of Antonio Candido (1992,1995), Mikael Bakhtin (2011), Umberto Eco (2005), Walter Benjamin (1994), Massaud Moises (1995), Leyla Perrone Moises (2006), among others.
Keywords: Chronic; Lourenco Diaferia; Representation mode; Represented contente; Concept of family